Electrostatic mechanism of bromine release during ozone depletion events - K. Yu. Tkachenko (Ukrainian Antarctic Journal, 2012)
In the investigation we discuss boundary layer ozone depletion events associated with spring and polar sea ice zone, special role of bromine in these processes and a viewpoint of author concerning mechanisms of bromine release in “fair weather” conditions and under high wind.